Targeted beta therapy of prostate cancer with 177Lu-labelled Miltuximab® antibody against glypican-1 (GPC-1) - Mei-Chun Yeh; Brian W. C. Tse; Nicholas L. Fletcher; Zachary H. Houston; Maria Lund; Marianna Volpert; Chelsea Stewart; Kamil A. Sokolowski; Varinder Jeet; Kristofer J. Thurecht; Douglas H. Campbell; Bradley J. Walsh; et al. (EJNMMI Research, 2020)
Abstract Purpose Chimeric antibody Miltuximab®, a human IgG1 engineered from the parent antibody MIL-38, is in clinical development for solid tumour therapy. Miltuximab® targets glypican-1 (GPC-1), a cell surface protein involved in tumour growth, which is overexpressed in solid tumours, including prostate cancer (PCa). This study investigated the potential of 89Zr-labelled Miltuximab® as an imaging agent, and 177Lu-labelled Miltuximab® as a targeted beta therapy, in a mouse xenograft model of human prostate cancer. Methods Male BALB/c nude mice were inoculated subcutaneously with GPC-1-positive DU-145 PCa cells. In imaging and biodistribution studies, mice bearing palpable tumours received (a) 2.62 MBq [89Zr]Zr-DFO-Miltuximab® followed by PET-CT imaging, or (b) 6 MBq [177Lu]Lu-DOTA-Miltuximab® by Cerenkov imaging, and ex vivo assessment of biodistribution. In an initial tumour efficacy study, mice bearing DU-145 tumours were administered intravenously with 6 MBq [177Lu]Lu-DOTA-Miltuximab® or control DOTA-Miltuximab® then euthanised after 27 days. In a subsequent survival efficacy study, tumour-bearing mice were given 3 or 10 MBq of [177Lu]Lu-DOTA-Miltuximab®, or control, and followed up to 120 days. Results Antibody accumulation in DU-145 xenografts was detected by PET-CT imaging using [89Zr]Zr-DFO-Miltuximab® and confirmed by Cerenkov luminescence imaging post injection of [177Lu]Lu-DOTA-Miltuximab®. Antibody accumulation was higher (% IA/g) in tumours than other organs across multiple time points. A single injection with 6 MBq of [177Lu]Lu-DOTA-Miltuximab® significantly inhibited tumour growth as compared with DOTA-Miltuximab® (control). In the survival study, mice treated with 10 MBq [177Lu]Lu-DOTA-Miltuximab® had significantly prolonged survival (mean 85 days) versus control (45 days), an effect associated with increased cancer cell apoptosis. Tissue histopathology assessment showed no abnormalities associated with [177Lu]Lu-DOTA-Miltuximab®, in line with other observations of tolerability, including body weight stability. Conclusion These findings demonstrate the potential utility of Miltuximab® as a PET imaging agent ([89Zr]Zr-DFO-Miltuximab®) and a beta therapy ([177Lu]Lu-DOTA-Miltuximab®) in patients with PCa or other GPC-1 expressing tumours.